Field Guide to Sharks, Rays and Chimaeras of the East Coast of North America - Ebert, David A. (Princeton University Press, 2024)
The definitive field guide to all the sharks, rays and chimaeras of eastern North AmericaThe waters off the East Coast of North America are home to an amazing variety of sharks, rays and chimaeras. This groundbreaking, comprehensive and easy-to-use field guide covers all 173 species found along the eastern seaboard of the United States and Canada, including Bermuda and the Bahamas, and extending into the Gulf of Mexico to the Yucatan Peninsula. These are all the species that are encountered in the shallow waters of estuaries and coasts and in the open ocean, including rarely seen deepsea species.Lavishly illustrated throughout, this must-have guide includes detailed species accounts describing key identification features, habitat, biology and status. It also features illustrated key guides that enable users to accurately identify species, comparison plates of similar species, dentition plates and illustrations of egg cases, where known. This an essential guide for fisheries management, trade regulation and shark conservation.The first field guide to cover all 173 speciesFeatures hundreds of color illustrations and photosDescribes key features, habitat, biology and statusIncludes depth guides, at-a-glance icons and distribution mapsOffers illustrated key guides, species comparisons and dentition plates
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Jun 2024)
Keywords: NATURE / Animals / Marine Life; Chimaeridae -- Identification; Chimaeridae -- Atlantic Coast (North America); Chimaeridae -- North America; Rays (Fishes) -- Identification; Rays (Fishes) -- Atlantic Coast (North America); Rays (Fishes) -- North America; Sharks -- Identification; Sharks -- Atlantic Coast (North America); Sharks -- North America